ChemInform Abstract: Highly Diastereoselective 1, 3‐Dipolar Cycloadditions of Chiral Non‐racemic Nitrones to 1, 2‐Diaza‐1, 3‐dienes: An Experimental and Computational Investigation. Issue 14 (April 2015) - Majer, Roberta; Konechnaya, Olga; Delso, Ignacio; Tejero, Tomas; Attanasi, Orazio A.; Santeusanio, Stefania; Merino, Pedro
Abstract: Cyclic nitrones (I), (IV), and (VI) give the products as single diastereomers under thermal conditions while nitrones (VIII) and (X) derived from D‐glyceraldehyde and D‐galactose give mixtures of diastereomers.